NATIONAL-CULTURAL SEMANTICS OF AGRICULTURAL TERMS IN ARTISTIC WORKS - Makhmudova Dilafruz Alijonovna (Bright Mind Publishing, 2025)
The article discusses the linguistic and linguocultural properties of agricultural terms in the literary text, which, in connection with the artistic thinking of the creator, serve as a metaphorical transfer or as a part of analogical devices and fulfill the linguocultural purpose, and therefore it is appropriate to determine the semantic properties of agricultural terms, like words, in the context of the text.
Keywords: Agricultural terms, terms, literary text, linguistic, linguocultural, metaphor, artistic and aesthetic whole, poetic actualization.